Suboptimal resource allocation scheme for scalable video multicast in integrated mobile WiMAX/WLANs network - Vishal A., Wankhede; R. More, Anant; Prasad, M.S.G. (International Journal of Engineering and Technology, 2018)
The goal of Resource Allocation Scheme (RAS) is to accomplish maximum usage of resources, assures Quality of Service (QoS), exploit throughput and diminish power consumption with viable algorithm complexity and scalability of system.Â RA algorithm for dynamicRASin downlink Mobile WiMAX is to maximize the minimum rate of user while satisfying power constraint. This study emphasizes on scalable video transmission in Downlink Mobile WiMax BS with 5 WLANâ€™s each comprised of 10 users with different QoS requirements. Convex optimization techniques in scheduling algorithms marginally improve the performance measure as compared to traditional iterative non-linear methods. This study proposes Active-Set optimization technique for power allocation (PA) amongst sub-carrier per Subscriber Station (SS) and Greedy Weighted Algorithm (GWA) for sub-carrier allocation. Finally simulation results show that the proposed GWA and Active-Set optimization technique can effectively achieve maximum network throughput and number of satisfied users.